MANAGING COMPETITIVENESS IN A GLOBALIZED WORLD - Jiang wenhan; Kozhakhmetova Asel (Scientific Research and Experimental Development, 2024)
Competitiveness management becomes essential to businesses’ success in the global marketplace in the setting of globalization. This article examines important tactics that assist businesses in striking a balance between local and global demands, such as the adaptation, aggregation, and arbitration (AAA) strategy. In addition to creating new opportunities and changing market conditions, digitalization and the platform economy also present businesses with ethical and data security challenges. Techniques like data analysis, technological investment, and a focus on sustainable development are crucial for guaranteeing long-term prosperity and helping businesses adjust to the quickly shifting global market conditions. In the current environment, where global marketplaces are growing increasingly integrated, businesses must implement creative management techniques. In order to succeed in the global arena, one must strategically pool resources in order to attain economies of scale, in addition to being able to adjust to local conditions. Access to new markets is made easier by digitization and platform solutions, but businesses also demand that they adhere to strict guidelines for data protection and transparency.